Distributed Feedback Lasers Based on MAPbBr3. Issue 4 (22nd January 2018) - Pourdavoud, Neda; Mayer, André; Buchmüller, Maximilian; Brinkmann, Kai; Häger, Tobias; Hu, Ting; Heiderhoff, Ralf; Shutsko, Ivan; Görrn, Patrick; Chen, Yiwang; Scheer, Hella‐Christin; Riedl, Thomas
Abstract: Hybrid perovskite semiconductors hold great promise as low‐cost, yet high performance gain media for lasers. Distributed feedback (DFB) resonator structures are a key to unlock low laser threshold levels, which are essential on the way to the first electrically operated perovskite laser diode. Here, the first DFB lasers based on methylammonium lead bromide (MAPbBr3 ) thin films, with a linear photonic grating imprinted into the MAPbBr3 active layers is presented. High‐Q Bragg resonator gratings with a periodicity of 300 nm are directly patterned by thermal nanoimprinting into thin films of MAPbBr3 at a temperature as low as 100 °C. A notable effect of the imprinting process is a substantial flattening of the initially very rough polycrystalline perovskite layers to layers consisting of large crystals on the order of tens of microns with a surface roughness of 0.6 nm. The smooth surface affords a significantly lowered threshold for the onset of amplified spontaneous emission due to reduced scattering. In optically pumped DFB laser structures, very low lasing thresholds of 3.4 µJ cm −2 are achieved. It is foreseen that these results will influence research on perovskite‐based optoelectronic devices beyond lasers, e.g., light emitting diodes and solar cells. Abstract : Distributed feedback (DFB) lasers based on methylammonium lead bromide (MAPbBr3 ) thin films are reported. Thermal nanoimprinting is used to prepare linear Bragg gratings into the MAPbBr3 active layers. A very low lasing threshold of 3.4 µJ cm −2 is achieved, which is indicative of the outstanding material quality of the imprinted MAPbBr3 layer.